Constitutive and interleukin-1 (IL-1)-inducible factors interact with the IL-1-responsive element in the IL-6 gene. - Isshiki, H (1990)
The interleukin-6 (IL-6) promoter is rapidly and transiently activated with other cytokines, including IL-1, tumor necrosis factor, and platelet-derived growth factor, as well as phorbol esters and agents that increase intracellular cyclic AMP. In this study, we have investigated cis-acting regulatory elements and trans-acting factors responsible for IL-1-induced IL-6 gene expression. Studies on the 5' deletion mutants of the human IL-6 gene suggested that the IL-1-responsive element was mapped within the IL-6 promoter region (-180 to -123) which was homologous to the c-fos serum-responsive enhancer element. Gel retardation assay identified two types of nuclear factors that bound to this region, one constitutive and the other inducible. These two factors recognized a 14-base-pair (bp) palindromic sequence, ACATTGCACAATCT. Furthermore, three copies of this 14-bp palindrome conferred IL-1 responsiveness to the basal enhancerless IL-6 promoter, indicating that a 14-bp-dyad symmetry sequence was an IL-1-responsive element in the IL-6 gene.